ТАЪЛИМ ЖАРАЁНИНИ ИНДИВИДУАЛЛАШТИРИШНИНГ ПЕДАГОГИК АСОСЛАРИ - Тўхтахўжаев, Х.Б. (SCIENCE and SOCIETY, 2017)
In the article there was analyzed the issue of realization of the principle of individualization in physical education of students in the system of continuous education.
Keywords: individualization; health; physical education; teaching innovation; pedagogics; psychology